THE PREVALENCE OF SELF-MEDICATION PRACTICE AMONG UNDERGRADUATE STUDENTS AT LIRA UNIVERSITY, LIRA DISTRICT. A CROSS-SECTIONAL STUDY. - Apio, Joan (Student’s Journal of Health Research Africa, 2023)
Background: The study aims to determine the prevalence of self-medication practice among undergraduate students, at Lira University, Lira district. Methodology: A cross-sectional study was conducted among undergraduate students, at Lira University. The study was conducted at Lira University. The university is located in Ayere village, Barapwo parish, Lira sub-county, Erute County in Lira district. It covers a total area of 621 acres (251.3 hectares). Lira University has 3 faculties i.e. faculty of Management Sciences, Health Sciences, and Education and it runs 17 programmes, with a total enrolment of 976 students (531 males and 445 females) by the academic year 2018/2019. The study population was all students enrolled in undergraduate programs at Lira University, Lira district. By use of the purposive sampling technique, Lira University undergraduate students were chosen. Stratified random sampling was used to divide the study population into strata of gender (male or female). Simple random sampling was used finally to identify the participants that were involved in the research from each stratum. Results: Out of those who participated in the study, 129(45.42%) were females and 155(54.58%) were male. The prevalence of self-medication was 82.95%. Conclusions: The prevalence of self-medication among undergraduate students was found to be 82.95% which was considerably high. Recommendations: National guidelines and policies on medical access should be developed, need for public medical insurance for all people in the community, needs to be investigated more on student-related factors.